(3JMQjQ cJGH XGgQGJ Gdadcs - (3GbdjOSs
(3ChdgG (B:s
(3jbhd eMeO GdWhSi de JbY Edi ef GdcJGH Yfg fSNI SbjeI ai ZGjI GdSbe s
(3BNQgG (B:s
(3hPdc GdfUa ef adc GdHQhL GdJi ai GdfUa aEf ReGf HJOjd cd hGMOI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1463s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs